THE INFLUENCE OF TOURISM FACILITIES AND PROMOTIONS ON THE INTEREST OF VISITING TOURISTS IN SUMBERINGIN BATH NATURAL TOURISM IN MALANG REGENCY - Mahmudatul Himma; Fullchis Nurtjahjani; Lilies Nur Aini; Muhamad Muwidha (International Journal of Economic Research and Financial Accounting, 2024)
The tourism sector is one of the pillars of the Indonesian economy and is a major contributor to foreign exchange. The growth of the tourism sector makes tourist destination managers compete to attract tourists to visit. The high interest of tourists in visiting can trigger the possibility of making a decision to visit a destination. The aim of this research is to determine the relationship between tourist facilities and promotions on visiting interest. The population in this study were tourists from the Sumberingin Bathing Nature Tourism. This research used a purposive sampling technique with a sample size of 100 tourists. The data collection method is through observation, interviews, questionnaires, while the data analysis method used is Multiple Linear Regression Analysis. The research results show that tourist facilities partially influence interest in visiting, promotions partially influence interest in visiting. The research results also show that tourist facilities and promotions simultaneously influence interest in visiting the Sumberingin Baths Nature Tourism.